The evaluation of conceptual design through dynamic simulation: A proposal based on TRIZ and system Dynamics. (November 2020) - Delgado-Maciel, Jesús; Cortés-Robles, Guillermo; Sánchez-Ramírez, Cuauhtémoc; García-Alcaraz, Jorge; Méndez-Contreras, Juan Manuel
Highlights: A methodology that combines some TRIZ tools with the System Dynamics approach. The use of TRIZ and System Dynamics simulation to propose and evaluate conceptual design. A tool to model inventive problems as functions to analyze their behavior through time. An analysis of conflicts in the system and the impact of a potential solution. Application of continuous simulation to the Substance-Field Modeling (SFM). Abstract: Conceptual design is a decisive stage in the new product development process and responsible for the originality and uniqueness of a product. Also, it is in this stage where technical feasibility becomes a critical issue in time. Simultaneously, there is an increasing pressure for developing new products faster, which demands more original, practical, and faster solutions from the conceptual design stage. This article demonstrates that the combination of the Theory of Inventive Problem Solving (TRIZ) with the System Dynamics Simulation can face this challenge. Results underline the following advantages: (1) The ability to assist the decision making process; (2) The capacity to identify the critical problem to solve; (3) The evaluation and simulation of conceptual design.